Contractual framework for design- bid- build contract to adopt Building Information Modeling in Jordan - Saraireh, Ibrahim Moh'd A. Q.; Ahmad Tarmizi, Haron (Blue Eyes Intelligence Engineering & Sciences Publication, 2020)
To provide contractual framework for Design-Bid-Build (DBB) contract as reference for construction industry in Jordan, this paper aims to discuss the best contractual framework to adopt Building Information Modeling (BIM) under (DBB) approach in construction sector in Jordan. To achieve this aim, scope of comprehensive literature divided in two frameworks is explored. First, the construction sector in Jordan and the others is the building information modeling framework. In this research, a qualitative approach is employed, where 13 semi-structured meetings were implemented with the largest construction companies in Jordanian construction field. The main research' findings revealed that improvements in the DBB contract, adopting BIM officially in contract and improving stakeholders ' relationship are obtained. The study concluded that to adopt BIM process correctly, earlier participation of major stakeholders is essential to enhance the coordination grade, discovering early disputes and decreasing the redesign processes. This in turn, safes efforts, time and cost.